Pendidikan Multikultural dalam Pendidikan Agama Islam: Analisis Kritis Perspektif Martin J. Beck Matuštík dan Judith M. Green - Zainuddin; Husnul Khatimah; St. Wardah Hanafie Das (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2026)
This article examines multicultural education in Islamic Religious Education (IRE) through a critical analysis of the perspectives of Martin J. Beck Matuštík and Judith M. Green. The study is motivated by the increasing cultural and social diversity of contemporary societies, which requires IRE to move beyond a purely normative orientation toward a more inclusive, dialogical, and justice-oriented approach. Using a qualitative library-based research method, this article analyzes the key works of both scholars and relates their ideas to the foundational values of Islamic education. The findings indicate that Matuštík emphasizes dialogical ethics, moral responsibility, and critical engagement with structural injustice as essential components of multicultural education. In contrast, Green highlights inclusivity, democratic participation, and critical awareness of power relations within multicultural contexts. These perspectives align closely with Islamic teachings that promote justice, compassion, and tolerance as core principles of social life. Therefore, integrating the ideas of Matuštík and Green into Islamic Religious Education can strengthen the development of an educational framework that is responsive to diversity and committed to fostering a harmonious and equitable society.